Atypical Aeromonas salmonicida vapA type V and Vibrio spp. are predominant bacteria recovered from ballan wrasse Labrus bergylta in Scotland - Papadopoulou, Athina; Wallis, Tim; Ramirez-Paredes, Jose Gustavo; Monaghan, Sean J; Davie, Andrew; Migaud, Herve; Adams, Alexandra (Diseases of Aquatic Organisms, 2020)
Healthy and/or moribund farmed and wild ballan wrasse Labrus bergylta (>0.5 to 900 g) were sampled from hatcheries (n = 2) and Atlantic salmon cage sites (n = 8) in Scotland between February 2016 and October 2018. Less than half of the sampled individuals (n = 43, 32.3%) had been vaccinated (autogenous polyvalent vaccine; dip and/or injection) against atypical furunculosis (type V and VI) while 20 (15.0%) fish were not vaccinated and the rest (70 individuals, 52.7%) were of unknown vaccination status. Swab samples from skin lesions, gill, liver, spleen and kidney were inoculated onto a variety of bacteriological agar plates and bacteriology identification and sequencing analysis was performed on significant bacterial colonies. Atypical Aeromonas salmonicida (aAs) vapA type V was the predominant bacterial species (70/215 bacteria isolates; 32.5% of bacteria samples – 43/117 positive individual fish; 36.8%) isolated in this survey followed by Vibrio species which were the most geographically prevalent bacteria. Photobacterium indicum/profundum was also isolated from L. bergylta for the first time during this study. The collection of these bacterial isolates provides useful information for disease management. Identifying the aAs isolates involved in disease in ballan wrasse could provide vital information for improving / updating existing autogenous vaccines.